2007
DOI: 10.1063/1.2783997
|View full text |Cite
|
Sign up to set email alerts
|

Kerr microscopy studies of microwave assisted switching

Abstract: We study microwave assisted magnetization reversal of elliptical Ni81Fe19 thin film elements employing Kerr microscopy. A microwave field is applied along the short axis of the element and orthogonally to a quasistatic magnetic field, which is parallel to the long axis of the element. The reversal process is characterized by the formation of a complex multidomain structure. We demonstrate that the reversal process in total is compressed by applying a sufficiently high microwave field, which assists to overcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11] Microwave-assisted magnetization reversal (MAMR) has been widely investigated for application to perpendicular magnetic writing in hard disk drives. [12][13][14][15][16] Very recently, a frequency-dependent reduction in the switching field of the magnetization was experimentally reported for CoCrPt-SiO 2 granular films with perpendicular anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] Microwave-assisted magnetization reversal (MAMR) has been widely investigated for application to perpendicular magnetic writing in hard disk drives. [12][13][14][15][16] Very recently, a frequency-dependent reduction in the switching field of the magnetization was experimentally reported for CoCrPt-SiO 2 granular films with perpendicular anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…Several other experiments confirmed the MAMR effect. Specifically, Grollier et al 5 demonstrated microwave-assisted reversal in cobalt strips by means of anisotropic magnetoresistance measurements; Nembach et al 6 and Pimentel et al 7 10,11 reported the observation of MAMR effects in Permalloy layers in magnetic tunnel junctions.…”
mentioning
confidence: 97%
“…6,7 The new approach presented here, however, allows the direct study of MAMR effects in bare samples, as explained below. Note that in Refs.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Following the work by Thirion et al, the MAMR response was confirmed in a number of different types of magnetic elements. These include single-domain elements, such as submicron cobalt particles 2 and micron-sized Permalloy film elements, 3 and multidomain materials, such as cobalt strips, 4 Permalloy thin films, 5,6 submicron-wide Permalloy wires, 7 and Permalloy layers in magnetic tunnel junctions. 8,9 In addition to the experimental work summarized above, the numerical simulations of MAMR processes have also been carried out on the basis of the torque equation of motion with damping.…”
Section: Introductionmentioning
confidence: 99%